Acceptability of the talking touchscreen for health literacy assessment. - Yost KJ; Webster K; Baker DW; Jacobs EA; Anderson A; Hahn EA; Yost, Kathleen J; Webster, Kimberly; Baker, David W; Jacobs, Elizabeth A; Anderson, Andy; Hahn, Elizabeth A (Journal of Health Communication)
Self-administration of a multimedia health literacy measure in clinic settings is a novel concept. Demonstrated ease of use and acceptability will help predicate the future value of this strategy. We previously demonstrated the acceptability of a "Talking Touchscreen" for health status assessment. For this study, we adapted the touchscreen for self-administration of a new health literacy measure. Primary care patients (n = 610) in clinics for underserved populations completed health status and health literacy questions on the Talking Touchscreen and participated in an interview. Participants were 51% women, 10% age 60+, 67% African American, 18% without a high school education, and 14% without any prior computer experience. The majority (93%) had no difficulty using the touchscreen, including those who were computer-naive (87%). Most rated the screen design as very good or excellent (72%), including computer-naive patients (71%) and older patients (75%). Acceptability of the touchscreen did not differ by health literacy level. The Talking Touchscreen was easy to use and acceptable for self-administration of a new health literacy measure. Self-administration should reduce staff burden and costs, interview bias, and feelings of embarrassment by those with lower literacy. Tools like the Talking Touchscreen may increase exposure of underserved populations to new technologies.